Handbook on Residential Property Prices Indices - Eurostat (Luxembourg: Publications Office of the European Union, 2014)
Residential property is both a source of wealth and, insofar as property owners live in or on their property, an important determining factor in their cost of living. The price of a house is something different from the cost of dwelling services it provides, though the two concepts are obviously interlinked. The need for property price indices that are fit-for-purpose was recognized at a conference organized jointly by the International Monetary Fund (IMF) and the Bank for International Settlements (BIS) in Washington DC, October 2003. As a result, a chapter on residential property price indices was added to the IMF's "compilation guide of financial soundness indicators". The idea of a more detailed handbook dates back to a workshop organized by the Organization for Economic Co-operation and Development (OECD) and the IMF on real estate price indices in Paris, November 2006. The aim of this handbook is to facilitate the setting-up of residential property price indices in countries where these are still missing and the improvement of existing price indices where this is deemed necessary. It is designed to give practical guidance on the compilation of house price indices, both in developed and less developed countries, and to increase international comparability of residential property price indices. It explains the different user needs, gives details on data and methods that can be used to compile residential property price indices, and provides recommendations. The production of the handbook was funded and supported by Eurostat.